Uji Aktivitas Formulasi Mikrokapsul Ekstrak Etanol Daun Pepaya (Carica papaya L.) sebagai Antidislipidemia terhadap Tikus Putih - Devin Rio Alvaro; Razoki Razoki; Muhammad Yunus (Lembaga Pengembangan Kinerja Dosen, 2025)
Dyslipidemia is a health problem characterized by impaired fat metabolism in the body, characterized by changes in blood lipid levels, either increasing or decreasing. This condition is generally seen through increased levels of total cholesterol, low-density lipoprotein (LDL), triglycerides, and decreased levels of high-density lipoprotein (HDL). This imbalance in the lipid profile, if persisted over the long term, has the potential to accelerate the formation of atherosclerotic plaque on artery walls, which can lead to cardiovascular disease. This study aims to determine the effectiveness of papaya leaf (Carica papaya L.) ethanol extract microcapsules in reducing cholesterol levels in white rats induced by a high-fat diet. The high-fat diet is formulated from a mixture of beef fat, eggs, and lard to increase cholesterol levels in a controlled manner. After the induction phase, the rats were divided into six treatment groups: a negative control group, a positive control group (simvastatin 0.36 mg), and three treatment groups with doses of papaya leaf ethanol extract microcapsules of 0.25%, 0.50%, and 0.75%. The treatment was given orally for 14 consecutive days. Total cholesterol levels were measured before and after treatment to evaluate the effectiveness of the intervention. The results showed that administration of papaya leaf extract microcapsules significantly reduced cholesterol levels. The 0.50% dose provided the most optimal effect, with a reduction reaching 77 mg/dL, greater than the simvastatin group. However, increasing the dose to 0.75% did not show a significant additional reduction effect, indicating an optimal dose-response point. Therefore, the 0.50% concentration can be considered the most effective dose and has the potential to be developed as an alternative natural cholesterol-lowering therapy. These findings also strengthen the potential use of papaya leaves as a bioactive source to support efforts to prevent and control dyslipidemia.